Equivalent transformations of geometric models - Хоменко, Інна Володимирівна (Eastern-European Journal of Enterprise Technologies, 2013)
The use of information technology is one of the few technologically and economically profitable ways of improvement of the production efficiency. The main tool of automation of design and technological units are computer- aided design systems. However, the CAD is not only the software, but also qualified personnel, procedures, etc. Most analysts agree on the opinion that the main problem of the introduction of computer systems in production is a personnel problem. That is why, the problems of development and implementation of effective information technologies in education acquire more importance. The article considers the questions that arise in the design of systems based on knowledge: data presentation and knowledge. The languages of knowledge representation were analyzed. Taking into account the drawbacks of the existing languages, a special language of representation of geometric models was developed in the system for automated training of disciplines, rich in engineering graphics.